ANTI-ELASTASE, ANTI-COLLAGENASE AND ANTIMICROBIAL ACTIVITIES OF THE UNDERUTILIZED RED PITAYA PEEL: AN IN VITRO STUDY FOR ANTI-AGING APPLICATIONS - Vijayakumar, Ramya; Abd Gani, Siti Salwa; Mohd Mokhtar, Nor Fadzillah (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To investigate the in vitro anti-elastase, anti-collagenase, and antimicrobial activities of the red pitaya peel extract for cosmetic application focusing on skin aging. Methods: Extraction was performed by the reflux method for 103 minutes at 56°C with 82% aqueous ethanol solution and the red pitaya peel extract was evaporated using a rotary evaporator. Anti-elastase and anti-collagenase properties were evaluated using the drug discovery kits (neutrophil elastase colorimetric and matrix metalloproteinase-1 colorimetric, respectively). The antimicrobial potential was analyzed using agar well diffusion method against 10 selected microorganisms, and the presence or absence of the inhibition zones was identified. Results: The red pitaya peel extract exhibited remarkable inhibition percentage 87.62±0.05% and 96.92±0.02% for anti-elastase and anti-collagenase activities, respectively. Red pitaya peel extract showed significant inhibition against the Gram-positive Bacillus subtilis B29 with an inhibition zone diameter of 8.0±0.3 mm. Conclusion: The excellent anti-aging properties displayed by the underutilized red pitaya peel extract highlighted its potential as a natural source of anti-aging agent for cosmetic formulations.